Morphological and Molecular Assessment in Thyroid Cytology Using Cell-Capturing Scaffolds - Scarpino, Stefania; Taccogna, Silvia; Pepe, Giuseppina; Papini, Enrico; D’Angelo, Martina; Cascone, Federica; Nicoletti, Daniele; Guglielmi, Rinaldo; Palermo, Andrea; Trombetta, Marcella; Rainer, Alberto; Taffon, Chiara; Crescenzi, Anna (Hormone and Metabolic Research, 2020)
The increased frequency of thyroid nodules is paralleled by the rise of thyroid cancer diagnosis. To define the nature of most thyroid nodules, fine needle aspiration (FNA) followed by cytological evaluation is considered the method of choice. About 20% of FNA biopsies on thyroid nodules, however, show indeterminate cytological features and may require diagnostic surgery. Several immunocytochemical and molecular markers have been proposed to improve classification of thyroid nodules, but these tests require adequate cell amount and cytological paraffin inclusion. Polymeric matrices were recently proposed for the collection of cells for diagnostic purposes. In this study, we evaluated the diagnostic use of a new matrix (CytoMatrix). Morphological, molecular and immunohistochemical investigations were carried out on 23 FNA samples included in CytoMatrix and compared with data obtained from the definitive histology of surgical samples. Our results showed that CytoMatrix is suitable to capture and preserve the cellularity of the samples harvested by FNA and that its paraffin sections mimic the morphology of those obtained from real histological tissue. Immunohistochemistry on CytoMatrix samples was consistent with the immunophenotypical profile of the corresponding histological surgical specimens. Mutational analysis of the BRAF (V600E) gene performed on CytoMatrix inclusions and paired surgical tissue matched in all but one cases while matrix immunohistochemistry identified 91.6% of BRAF mutated samples. In conclusion, we suggest that CytoMatrix could be a reliable tool to overcome the current limits of traditional collection methods for the study of thyroid cytology, thereby improving their reliability for a conclusive diagnostic interpretation.
Keywords: thyroid cytology; cellblock; CytoMatrix; immunohistochemistry; indeterminate cytology; cytological samples